Urban Sustainability Indicators Systems:: The Challenges of the Process of Measurement, Analysis and Monitoring - Martins, Maria de Fátima; Cândido, Gesinaldo Ataíde (Sustainability in Debate, 2015)
Indicator systems support public policies and sustainable management of cities. This paper aims to identify the challenges of the construction process of urban indicator systems for the analysis and monitoring of the sustainability of urban areas. A theoretical discussion on sustainability and urban indicator systems is offered, with a focus on the main challenges presented by this issue. The essay shows that the construction of sustainability indicator systems that serve to support urban public policies should be based on the understanding of urban spaces. Such spaces should be investigated by adopting a comprehensive theoretical concept of urban problems, covering the various dimensions of sustainability. Furthermore, appropriate methodologies to reduce the subjectivity of sustainability indicators and some of their weaknesses in terms of availability, quality and updating of data, giving those systems the capacity to provide information to support sustainable urban development.